Kesiapan Memasuki Sekolah Dasar Pada Anak di TKIT Attaqwa Gumawang Tahun 2016 - Eka Marwati; Sholeh Hasan; Dwi Andriani (Indonesian Journal of Educational Counseling, 2017)
Education becomes an essential thing in human development and nation progress. Phenomenon of elementary school test that should become an interesting thing, is a new scourge for students and parents. Competency demand that should be qualified by new student rises without noticing student readiness for attending primary school. This research is aimed to know readiness for attending school on TKIT students Attaqwa Gumawang. The research is applied on 59 students of TKIT Attaqwa Gumawang. The data is obtained by 10 sub tests that reveal development aspects of school age-children. The result data is analyzed by using analysis technique of descriptive quantitative. The research result shows all aspects that are required for student readiness for attending primary school are generally mature. Qualitatively, some aspects for attending primary school that related with cognitive aspect are observation, ability to distinguish, understanding about large, quantity and comparison, sharpness of observation, critical observation, concentration, memory and understanding story are some aspects that have already reached to maturity level optimally. Besides, the maturity level some aspects that related with fine and gross motoric ability, assessment aspect toward situation and personal picture are not optimal yet.